2017
DOI: 10.1111/cgf.13170
|View full text |Cite
|
Sign up to set email alerts
|

Visual Comparison of Eye Movement Patterns

Abstract: In eye tracking research, finding eye movement patterns and similar strategies between participants’ eye movements is important to understand task solving strategies and obstacles. In this application paper, we present a graph comparison method using radial graphs that show Areas of Interest (AOIs) and their transitions. An analyst investigates a single graph based on dwell times, directed transitions, and temporal AOI sequences. Two graphs can be compared directly and temporal changes may be analyzed. A list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…In this paper, we use state-of-the-art visualization techniques to analyze our eye movement data. We compare participants' line viewing behavior using radial transition graphs [6] and parallel scanpaths [7] to inspect the eye movement data over time. The radial transition graphs allow us to investigate the distribution of fixation duration for multiple lines as well as inspect transitions between individual lines in a compact manner.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we use state-of-the-art visualization techniques to analyze our eye movement data. We compare participants' line viewing behavior using radial transition graphs [6] and parallel scanpaths [7] to inspect the eye movement data over time. The radial transition graphs allow us to investigate the distribution of fixation duration for multiple lines as well as inspect transitions between individual lines in a compact manner.…”
Section: Related Workmentioning
confidence: 99%
“…However, there are not many visualization tools available for eye tracking researchers to use. To bridge this gap, we leverage two visualization techniques namely radial transition graphs [6] and parallel scanpaths [7] introduced in prior work to help us analyze the data from the eye tracking study presented here and show the viability of using visualizations for eye tracking analysis in program comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…We used a quantitative and qualitative approach to analyze the eye movement data. Using the radial transition graph visualization technique [Blascheck et al 2017b] we found that natural language text is read in a more linear fashion and that participants focus more on important parts of source code. We were also able to extract common patterns, analyze different reading behavior, and explore general strategies of participants using the radial transition graph.…”
Section: Discussionmentioning
confidence: 99%
“…Because our study dealt with short code snippets, we did not use the visualization techniques presented above. Instead, we use the radial transition graph [Blascheck et al 2017b] to determine and inspect transition sequences. This technique is available online (http://www.…”
Section: Visualizing Eye Tracking Datamentioning
confidence: 99%
“…This section focuses on the work related to doughnut charts and pie charts. These charts have been extensively used in different applications [WZM*16, SWLL13, LCWL14, MMWC17], such as sport analytics [WLS*18], urban informatics [CYW*16, LWL*17], weather forecast [KTB*18], medical and health data analysis [HPvU*18, CWS*17] and user behaviour analysis [BSBE17, WWL*10, CLS*12].…”
Section: Related Workmentioning
confidence: 99%